2022
DOI: 10.1186/s13023-022-02210-2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary peripheral chondrosarcoma arising in solitary osteochondroma: variables influencing prognosis and survival

Abstract: Background Secondary peripheral chondrosarcomas arising in solitary osteochondromas is an unusual complication, reported in small series. In this study, we aimed to present our experience with this rare variant of chondrosarcoma and compare results with already published data in order to determine prognostic factors for overall and disease-free survival. Methods The case study includes retrospective data from patients diagnosed at a single institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Accurate prediction for chondrosarcoma survival is crucial for the counseling, follow-up, and treatment planning of patients. Previous studies have revealed various prognostic factors influencing the survival times of patients with chondrosarcoma, including patient age, tumor size, histological type, tumor grade, and metastasis ( 6 , 19 21 ).. At the same time, increasing amounts of imaging ( 22 , 23 ) and genetic data ( 2 , 24 ) are being mined for survival analysis of chondrosarcoma patients. In the face of high-dimensional data, the limitations of the linear relationship between variables assumed by the classical CoxPH model are evident ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate prediction for chondrosarcoma survival is crucial for the counseling, follow-up, and treatment planning of patients. Previous studies have revealed various prognostic factors influencing the survival times of patients with chondrosarcoma, including patient age, tumor size, histological type, tumor grade, and metastasis ( 6 , 19 21 ).. At the same time, increasing amounts of imaging ( 22 , 23 ) and genetic data ( 2 , 24 ) are being mined for survival analysis of chondrosarcoma patients. In the face of high-dimensional data, the limitations of the linear relationship between variables assumed by the classical CoxPH model are evident ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…They proposed that secondary peripheral chondrosarcomas have a low-grade behavior and that, when possible, wide surgical excision is the best treatment option for those that arise in solitary osteochondromas. The tumor's location does not affect prognosis, but accurate histological grade assessment correlates with tumor aggressiveness, and longterm follow-up is required for this rare variant of chondrosarcoma [18]. Ahmed et al reviewed 107 patients with secondary chondrosarcoma arising from a single osteochondroma (61 patients) or multiple exostoses (46 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, подтвержденный по результатам лучевого обследования вторичный характер опухоли на фоне остеохондромы позволил при первичной операции выбрать органосохраняющий объем. При опухолях G2 центральной локализации пациентам показана сегментарная резекция с эндопротезированием, при периферической локализации (на фоне остеохондромы, как в данном случае) зачастую возможно удаление опухоли с краевой резекцией кости, что и было сделано [40,41].…”
Section: Discussionunclassified